World Heart Federation Roadmap for Hypertension - A 2021 Update - Panniyammakal Jeemon; Tania Séverin; Celso Amodeo; Dina Balabanova; Norm R. C. Campbell; Dan Gaita; Kazuomi Kario; Taskeen Khan; Rita Melifonwu; Andrew Moran; Elijah Ogola; Pedro Ordunez; et al. (Ubiquity Press, 2021)
The World Heart Federation (WHF) Roadmap series covers a large range of cardiovascular conditions. These Roadmaps identify potential roadblocks and their solutions to improve the prevention, detection and management of cardiovascular diseases and provide a generic global framework available for local adaptation. A first Roadmap on raised blood pressure was published in 2015. Since then, advances in hypertension have included the publication of new clinical guidelines (AHA/ACC; ESC; ESH/ISH); the launch of the WHO Global HEARTS Initiative in 2016 and the associated Resolve to Save Lives (RTSL) initiative in 2017; the inclusion of single-pill combinations on the WHO Essential Medicines' list as well as various advances in technology, in particular telemedicine and mobile health. Given the substantial benefit accrued from effective interventions in the management of hypertension and their potential for scalability in low and middle-income countries (LMICs), the WHF has now revisited and updated the 'Roadmap for raised BP' as 'Roadmap for hypertension' by incorporating new developments in science and policy. Even though cost-effective lifestyle and medical interventions to prevent and manage hypertension exist, uptake is still low, particularly in resource-poor areas. This Roadmap examined the roadblocks pertaining to both the demand side (demographic and socio-economic factors, knowledge and beliefs, social relations, norms, and traditions) and the supply side (health systems resources and processes) along the patient pathway to propose a range of possible solutions to overcoming them. Those include the development of population-wide prevention and control programmes; the implementation of opportunistic screening and of out-of-office blood pressure measurements; the strengthening of primary care and a greater focus on task sharing and team-based care; the delivery of people-centred care and stronger patient and carer education; and the facilitation of adherence to treatment. All of the above are dependent upon the availability and effective distribution of good quality, evidencebased, inexpensive BP-lowering agents.